Theoretical studies of ⁶³Cu Knight shifts of the normal state of YBa₂Cu₃O₇ - Kuang, M.Q.; Wu, S.Y.; Zhang, Z.H.; Song, B.T. (Condensed Matter Physics, 2011)
The ⁶³Cu Knight shifts and g factors for the normal state of YBa₂Cu₃O₇ in tetragonal phase are theoretically studied in a uniform way from the high (fourth-) order perturbation formulas of these parameters for a 3d⁹ ion under tetragonally elongated octahedra. The calculations are quantitatively correlated with the local structure of the Cu²+(2) site in YBa₂Cu₃O₇. The theoretical results show good agreement with the observed values, and the improvements are achieved by adopting fewer adjustable parameters as compared to the previous works. It is found that the significant anisotropy of the Knight shifts is mainly attributed to the anisotropy of the g factors due to the orbital interactions. Зсуви Найта ⁶³Cu i g фактори в основному станi YBa₂Cu₃O₇ в тетрагональнiй фазi вивчаються теоретично в єдиному пiдходi з формул теорiї збурень високого (четвертого) порядку цих параметрiв для 3d⁹ iона в тетрагонально видовженому октаедрi. Розрахунки кiлькiсно корелюють з локальною структурою Cu²+(2) вузла в YBa₂Cu₃O₇. Теоретичнi результати демонструють добре узгодження зi спостережуваними значеннями, i покращення досягається шляхом використання меншої кiлькостi пiдгоночних параметрiв нiж у попереднiх роботах. Знайдено, що значна анiзотропiя зсувiв Найта є в основному атрибутом анiзотропiї g факторiв завдяки взаємодiї.